Qañ gétā Yoftāḥé Něgusé - Yoḥanes ʼAdmāsu (ʼAdis ʼAbabā yunivarsiti pěres, 2004)
A biography of Yoftahe Neguse, one of the modern pioneer poets of Ethiopia
Includes bibliographical references (pages 273-276)
Keywords: Biografie; Yoftāḥé Neguśé